The Effect of Acupressure at the SP6 and LI4 Points on the Reduction of Menstrual Pain (Dysmenorrhea) Among Adolescent Girls in the Anak Tuha Health Center Service Area, Central Lampung Regency - Fuji Lestari; Sri Nowo Retno; Yetty Dwi Fara; Yona Desni Sagita (Sean Institute, 2026)
Menstrual pain (dysmenorrhea) is a common reproductive disorder among female adolescents that can disrupt daily activities and diminish academic concentration. Management of dysmenorrhea involves both pharmacological and non-pharmacological approaches, including acupressure therapy at the SP6 (Sanyinjiao) and LI4 (Hegu) points, which are believed to enhance blood circulation and stimulate endorphin production to alleviate pain. This study aimed to determine the effect of acupressure at the SP6 and LI4 points on reducing menstrual pain among female adolescents at Islamic Junior High Schools (MTs) within the Anak Tuha Health Center service area, Central Lampung Regency, in 2025. A pre-experimental design with a one-group pretest-posttest approach was utilized, involving 25 respondents experiencing dysmenorrhea selected through total sampling. Data analysis using the Wilcoxon test revealed that the average menstrual pain scale decreased significantly from 4.48 (moderate pain) before the intervention to 1.32 (mild pain) after the intervention, with a p-value of 0.000 (p < 0.05). These findings indicate a significant effect of acupressure at the SP6 and LI4 points on reducing menstrual pain intensity. In conclusion, acupressure at the SP6 and LI4 points is effective in decreasing dysmenorrhea in female adolescents; therefore, it is recommended that students practice this technique independently as a non-pharmacological alternative, and that schools and healthcare providers offer education on safe, natural pain management.